Partai Mahasiswa dan Politik Oligarki di Indonesia - Shohibul Anshor Siregar (Jurnal Intervensi Sosial dan Pembangunan, 2022)
This study focuses on the establishment of the Indonesian Student Party (PMI) on January 21, 2022. Most of the alleged political analysts believe that this is part of a movement that aims to break solidarity to fight for student protests demands nationally. However, this article wants to explore a much bigger motive than that. PMI is not an ordinary political party. PMI's collaboration design with the strong current of identity politics behind the metamorphosis of the 1945 Indonesian Christian Party (Parkindo) which greatly determined its existence, is of course very important not to be seen except as a democratic anomaly in the midst of the divisions that flared up, especially during the leadership of President Joko Widodo.Keywords: Student Party, Student Movement, Identity Politics, Oligarchy, World-System Perspective.